THU0432 Pericardial effusion is an independent factor predictive of scleroderma renal crisis. (12th June 2018) - Fujisawa, Y.; Hara, S.; Zoshima, T.; Ito, K.; Mizushima, I.; Fuji, H.; Yamada, K.; Kawano, M.
Abstract : Background: Scleroderma renal crisis (SRC) adversely affects renal and patient survival in systemic scleroderma (SSc)[. 1, 2 The survival rate of SRC has been improved dramatically by angiotensin-converting enzyme inhibitor therapy, but SRC still has a poor prognosis. 3 Factors predictive of SRC include early diffuse skin involvement, rapid skin thickening, anti-RNA polymerase (RNAP) III antibodies, arthralgia/synovitis, and high glucocorticoid dosage. 4 Although classical data have implicated pericardial effusion as another predictive factor of SRC, 5 its role in SRC has not been well established. Objectives: To clarify the clinical impact of pericardial effusion as a predictor of SRC. Methods: Ninety-five patients diagnosed with SSc at our hospital between January 2003 and December 2017 were enrolled in the study. They were divided into a pericardial effusion group (n=21) and non-pericardial effusion group (n=74), and their clinical features retrospectively compared. Cox-regression analysis was performed to identify factors predictive of SRC. Results: The patients comprised 14 men and 81 women with an average age of 57.4 years (range, 14 to 82) and the mean observation period was 65 months (range, 1 to 125). Pericardial effusion was detected in 21 of 95 (22.1%) cases. In the pericardial effusion group, SRC, modified Rodnan's total skin thickness score (mRSS), C-reactive protein, maximum glucocorticoid dose, proteinuria, finger apex ulcers, and interstitial pneumonia were significantly more prevalent compared to the non-pericardial effusion group. Cox regression analysis indicated that pericardial effusion (hazard ratio; HR 11.8 [95% CI 1.6–84.6], p=0.014) and anti-RNAP III antibodies (HR 11.1 [95% Cl 2.0–59.6], p=0.005) were independent risk factors for SRC, while mRSS (HR 1.0 [95% CI 0.9–1.1], p=0.12), finger apex ulcers (HR 0.57 [95% CI 0.073–4.2], p=0.57), max glucocorticoid dose (HR 1.0 [95% CI 0.9–1.0, p=0.89]), and interstitial pneumonia (HR 0.9 [95%CI 0.2–3.7], p=0.96) were not. In the Kaplan-Meier method, SRC was significantly increased in the pericardial effusion group compared to non-pericardial effusion group (p<0.0001 by log rank test). Conclusions: Pericardial effusion is another independent factor predictive of SRC in addition to anti-RNAP III antibodies. References: [1] Steen VD, et al. Scleroderma renal crisis. Rheum Dis Clin North Am2003;29:315–33. [2] Hamaguchi Y, et al. Clinical and immunologic predictors of scleroderma renal crisis in Japanese systemic sclerosis patients with anti-RNA polymerase III antibodies. Arthritis Rheumatol2015;67:1045–52. [3] Penn H, et al. Scleroderma renal crisis: patient characteristics and long-term outcomes. QJM2007;100:485–94. [4] Woodworth TG, et al. Scleroderma renal crisis and renal involvement in systemic sclerosis. Nat Rev Rheumatol2016;12:678–91. [5] Steen VD, et al. Factors predicting development of renal involvement in progressive systemic sclerosis. Am J Med1984;76:779–86. Disclosure of Interest: None declared